2013
DOI: 10.1007/s00066-013-0411-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of tumor volume for radiotherapy outcome in patient with T2 laryngeal cancer

Abstract: Large TV worsen prognosis of patients with T2 laryngeal cancer. A large TV is more common for supraglottic, poorly differentiated tumors and may suggest higher risk of nodal spread. The routine estimation of TV prior to therapy may be essential in order to select the best treatment option for patients with T2 laryngeal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…Patients with SD ≤ 5 months had reduced LC ratio and over 2 times higher risk of local failure. This observation is in concordance with our pervious report [6] but had not been described before. Beside the primary tumor localization in the supraglottic area, also rapid tumor proliferation and fast progression of TV may be the reason of early symptoms.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Patients with SD ≤ 5 months had reduced LC ratio and over 2 times higher risk of local failure. This observation is in concordance with our pervious report [6] but had not been described before. Beside the primary tumor localization in the supraglottic area, also rapid tumor proliferation and fast progression of TV may be the reason of early symptoms.…”
Section: Discussionsupporting
confidence: 94%
“…Hereby we also found that patients with lower Hb concentration presented significantly poorer OS rate. Beside this, the negative relationship between Hb and TV was found what is in concordance with our previous observation for both, glottic and supraglottic tumors [6]. Negative correlation between Hb concentration and TV was also found by Stadler [22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Several authors [2,25,27,28] have discussed the role of incorporating tumor stage, HPV/p16 status, and smoking habits in oropharyngeal cancer patients in order to subdivide patients into different risk groups. Inflammatory scoring systems may have the potential to play a similar important role if analyzed consequently in well-characterized treatment groups.…”
Section: Resultsmentioning
confidence: 99%